Mechanical and thermal properties of poly(lactic acid) plasticized with dibutyl maleate and fumarate isomers: Promising alternatives as biodegradable plasticizers. (5th January 2021) - Llanes, Luana C.; Clasen, Samuel H.; Pires, Alfredo T.N.; Gross, Idejan P.
Graphical abstract: Highlights: Dibutyl maleate and fumarate induces the plasticization of poly(lactic acid) Plasticizers cis–trans isomerism affects thermal and mechanical properties. Dibutyl fumarate (trans) more efficiently plasticizes PLA than dibutyl maleate (cis) To observe the plasticizing effect, a content threshold must be reached. Abstract: The use of plasticizers, polymer blends and composites have been reported as effective strategies to overcome the rigidity and brittleness of PLA, drawbacks that commonly limits its application. In this study poly(lactic acid) was plasticized with 7 and 12 wt% of dibutyl esters of maleic or fumaric acid. The choice of plasticizer was motivated by recent studies reporting the biodegradability of maleic and fumaric esters and their efficiency as green plasticizers. This current study evaluates how the chemical structure, specifically the cis–trans isomerism of the plasticizer, can affect the plasticizing properties on PLA. The thermal and mechanical properties of the plasticized specimens were evaluated by DSC, DMA, Stress-Strain and Relaxation tests. The results indicated that samples plasticized with dibutyl fumarate exhibited a lower glass transition temperature (Tg), lower Young's modulus, and higher elongation at break than specimens plasticized with dibutyl maleate.